Carrot or Stick? Contract Frame and Use of Decision‐Influencing Information in a Principal‐Agent Setting - FREDERICKSON, JAMES R.; WALLER, WILLIAM (Journal of Accounting Research, 2005)
ABSTRACT A fundamental management accounting issue is how to incorporate decision‐influencing information (e.g., an ex post state signal) into employment contracts. Our experiment examines the effects of contract framing on such information use in a principal‐agent setting. In each of 40 rounds, participants (as employer and worker) negotiate a contract that specifies pay depending on an ex post state signal. State‐signal pay is framed as either a bonus or a penalty over two groups. The results show that the bonus frame facilitates information use, because of worker loss aversion. Although both groups initially underweigh the state signal, the bonus group quickly converges toward the optimal weight, whereas the penalty group persistently underweighs the state signal.